Aberrant Alternative Splicing Is Another Hallmark of Cancer - Michael Ladomery (International Journal of Cell Biology)
The vast majority of human genes are alternatively spliced. Not surprisingly, aberrant alternative splicing is increasingly linked to cancer. Splice isoforms often encode proteins that have distinct and even antagonistic properties. The abnormal expression of splice factors and splice factor kinases in cancer changes the alternative splicing of critically important pre-mRNAs. Aberrant alternative splicing should be added to the growing list of cancer hallmarks.